Obstetric and neonatal complications in pregnancies conceived after oocyte donation: a systematic review and meta‐analysis. (5th September 2016) - Storgaard, M; Loft, A; Bergh, C; Wennerholm, UB; Söderström‐Anttila, V; Romundstad, LB; Aittomaki, K; Oldereid, N; Forman, J; Pinborg, A
Abstract : Background: Approximately 50 000 oocyte donation (OD) treatment cycles are now performed annually in Europe and the US. Objectives: To ascertain whether the risk of adverse obstetric and perinatal/neonatal outcomes is higher in pregnancies conceived by OD than in pregnancies conceived by conventional in‐vitro fertilisation (IVF)/intracytoplasmic sperm injection (ICSI) or spontaneously. Search Strategy: A systematic search was performed in the PubMed, Cochrane and Embase databases from 1982–2016. Primary outcomes were hypertensive disorders of pregnancy, pre‐eclampsia (PE), gestational diabetes mellitus, postpartum haemorrhage, caesarean section, preterm birth, low birthweight and small for gestational age. Selection criteria: Inclusion criteria were original studies including at least five OD pregnancies with a control group of pregnancies conceived by conventional IVF/ICSI or spontaneous conception, and case series with >500 cases reporting one or more of the selected complications. Studies not adjusting for plurality were excluded. Data collection and analysis: Thirty‐five studies met the inclusion criteria. A random‐effects model was used for the meta‐analyses. Main results: For OD pregnancies versus conventional IVF/ICSI pregnancies the risk of PE was adjusted odds ratio (AOR) 2.11 (95% CI, 1.42–3.15) in singleton and AOR 3.31 (95% CI, 1.61–6.80) in multiple pregnancies. The risks of preterm birth and low birthweight in singletons were AOR 1.75 (95% CI, 1.39–2.20) and 1.53 (95% CI, 1.16–2.01), respectively. Conclusions: OD conceptions are associated with adverse obstetric and neonatal outcomes. To avoid the additional increase in risk from multiplicity, single‐embryo transfer should be the choice of option in OD cycles. Tweetable abstract: Oocyte donation pregnancies have increased risk of a range of obstetric and neonatal complications. Tweetable abstract: Oocyte donation pregnancies have increased risk of a range of obstetric and neonatal complications. This article includes Author Insights, a video abstract available athttps://vimeo.com/rcog/authorinsights14257 .